The Impact of Study Abroad Programs on Local Communities in Nepal: A Case Study Approach - Daman Bahadur Singh (Interdisciplinary Journal of Management and Social Sciences, 2025)
This study looks at to analyse the socio-cultural and economic impacts of study abroad programs on local communities in Nepal and to examine how the migration of students for education abroad influences local resource allocation and community development in Nepal. It investigates the knock-on effects on labor markets, community development, and cultural practices using a qualitative exploratory design. Semi-structured interviews, focus groups, and secondary sources such as government documents and regional economic indicators were some of the techniques utilized to collect data. The findings indicate that the out-migration of skilled labor, particularly in the agricultural, community-based, and small company sectors, has resulted in a notable decline in local productivity. Additionally, a decline in cultural participation has eroded social ties and customs. Furthermore, the dearth of qualified experts has increased the burden on economic activity, which has slowed down market expansion and local development. This was well illustrated by the research, which found that migration for education has far-reaching effects that go beyond a person’s academic pursuits since it upends established economies and local labor markets. It was discovered that developing countries plagued by this issue exhibit a variety of signs of their diminishing cultures due to modernization. The report emphasizes the need for policies that protect cultural assets and makes a demand for the implementation of proactive measures to maintain competent human resources through local employment and educational opportunities. Future studies should examine the long-term effects of migration, the reintegration of returning migrants, and an evaluation of Nepal’s current brain drain policies.